Dylematy terapeutycznej wielokulturowości. Pomiędzy swojskością a innością - Teusz, Grażyna (Kultura-Społeczeństwo-Edukacja, 2016)
The article is an attempt to analyze the phenomenon of multiculturalism and the issues to accompany in the context of building and achieving human identity. The main emphasis is placed on presenting the psychosocial dimension of constructing identity and its interactive character. Social identity is the other essential part of the issue next to individual identity. The objects of the author’s attention here are therapeutic implications and dilemmas presented in the context of multiculturalism.